Análise crítica sobre o uso da inteligência artificial nas decisões judiciais - Gonçalves, Laura Teixeira Rosa (2022)
This article briefly addresses the critical analysis of the use of Artificial Intelligence in judicial decisions. Initially, it addresses the tragedy of Justice in Brazil, explaining the costs present in the daily routine of the judiciary. After a brief explanation about costs and revenue of the national justice system, it is discussed if the use of Artificial Intelligence in the judiciary would be a viable solution to reduce the costs generated by the Judiciary. Then, Artificial Intelligence is conceptualized and its current use in the Judiciary is exemplified. Finally, concerns and care that should be thaken in the implementation of this new tecnology of Artificial Intelligence are addressed